DETERMINATION OF MENTHOL IN CANDY "TRAVISIL": UDC 543.544:547.596.2 (Bulletin of the Taras Shevchenko National University of Kyiv. Chemistry, 2013)
Conditions of the liquid- liquid extraction and gaschromatography analysis of  menthol in  candy  "Travisil" were optimized. Samples of candy  "Travisil" was analyzed in these conditions.
Keywords: liquid-liquid extraction, menthol, gaschromatography analysis